(3TQM GdQSGdI GdYVOjIs - (3Ydj GdSeQbfOjs
(3ChdgG (B:s
(3GdMeO ddg (B... (3adeG TGY aj GdCeUGQ hXgQ XghQ GdTeS aj GdfgGQ GdQSGdI GdYVOjI GdJj CaGOgG Gdehdi GdEeGe GdeMbb (B.. (3YVO GdMb hGdOjf (B.. (3hcGfJ eTJedI Ydi eSGFd hObjbI hJMbjbGJ YejbI eY ZGjI GdEjLGR (B...s
(3BNQgG (B:s
... (3eG PcQ Gf GdeYJHQ aj GdCdaGX hMGd GdhVY hGdehVhY dg aj (B... (3cdj hEf GSJYed ggfG aj eTNU adG jchf LRFjG HNdGa RjO aEfg LRFj dhUag dPdc GdeTNU hcPG GdMGd aj eKd gPg GdUhQI (B.s
(3GdJhKjbGJ GdeQLYjI (B:s
(3cTa GdXfhf (B1\898s
(3cTa GdXfhf (B1\898s
(3eUOQ GbJfGA GdCUd (B:s
(3cGTa GdZWGAs
(3ehGUaGJ GdhYGA (B:s
Keywords: (3GdHdGZIs